Medroxyprogesterone Acetate Antagonizes the Effects of Estrogen Treatment on Social and Sexual Behavior in Female Macaques - PAZOL, KAREN (2004)
Medroxyprogesterone acetate (MPA) commonly is used in contraception and hormone replacement therapy. However, little is known about its effects within the central nervous system. Using ovariectomized pigtail macaques (Macaca nemestrina), we evaluated the potential for MPA to antagonize estradiol (E2) effects on female sociosexual behavior. Subjects (n = 6) were treated sequentially with placebo, E2 alone, E2 + progesterone (P4), and E2 + MPA. The order of treatments was balanced among subjects, and equimolar quantities of P4 and MPA were administered. During each treatment period, female sexual initiation rates, anxiety-related behavior, and aggression were recorded. Treatment with E2 alone induced a substantial rise in female sexual initiation rates. Although concurrent P4 treatment failed to significantly inhibit sexual behavior, MPA treatment markedly antagonized E2’s effects. Neither the E2-only nor the E2 + P4 treatment had an impact on aggression rates, but the E2 + MPA treatment induced a significant rise in this behavior. Both MPA and P4 counteracted the effect of E2 on measures of anxiety. These findings suggest that MPA antagonizes certain behavioral effects of E2 that may be beneficial to women, and that it does so more profoundly or in ways that endogenous P4 does not. The marked increase in aggression seen during MPA treatment suggests that production of negative affect may be a particularly serious side effect of MPA.